Caracterização fenotípica e molecular da resistência a clindamicina em isolados clínicos de Staphylococcus aureus de um hospital terciário - Bottega, Angelita (2016)
Staphylococcus aureus demonstrated over the time, the ability to develop resistance to the most antimicrobials. The mechanism of resistance to macrolides in S. aureus also reaches lincosamides and streptogramins B, featuring the designate MLSB resistance, whose expression can be constitutive (cMLSB) or inducible (iMLSB) and it is encoded mainly by the presence of erm genes (ermA, ermB and ermC) and msrA. The cMLSB resistance is easily detected by susceptibility testing used in routine laboratory, but iMLSB resistance identification is only possible by using an inducing agent. Thus, clindamycin therapy in cases of infection by isolated with iMLSB resistance can fail. Thus, this study aimed to characterize the phenotypic profile (cMLSB e iMLSB) and molecular (presence of ermA, ermB, ermC and mrsA genes) of 140 clinical isolates of methicillin-sensitive S. aureus (MSSA) and methicillin-resistant (MRSA), from patients admitted at University Hospital of Santa Maria (HUSM) in the period from April to December 2011.The inclusion criteria were all isolates identified as S. aureus by manual phenotypic methods (Gram stain, catalase test, coagulase, etc.) and automated (MicroScan® - Siemens), and excluded of the study repeated samples from the same patient. The MLSB phenotype was detected by approaching disk induction test (D-test), and from 140 strains, 25 had cMLSB phenotype and 11 the iMLSB phenotype. Of constitutive isolates, 20 were MRSA and 5 MSSA, while the inducible isolates 8 (5.8%) were MSSA and 3 (2.1%) MRSA. From these results, we performed the molecular characterization by Reaction technique Polymerase Chain (PCR) of all isolates that expressed the MLSB resistance in phenotypic test. Among these, ermA and ermC genes were prevalent, identified at 11 and 15 of the isolates, respectively. The gene ermB amplified in 4of 36 strains, while msrA in 13, and of these, 8 had an association with the erm genes surveyed. Despite the iMLSB phenotype have been less frequent than cMLSB, the realization of the D-test is important to detect these phenotypes, it may guide therapeutic procedures, helping to improve in the health of the patient, reducing the length of hospitalization and thus the burden on the health system. Moreover, the test is inexpensive and easy to run compared to the PCR technique, which despite its high sensitivity and specificity is not used in routine of all clinical laboratories due to high costs.